Influence of Parity on Health Seeking Behaviours among Pregnant Women Infected with Sexually Transmitted Infections (STIs) in Delta State, Nigeria - Ugwuoke, Anthony C.; Njoku, Patrick Ndionyenma; Agambi, Okoi Princewil (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2025)
The study determined health seeking behaviours (HSBs) among pregnant women infected with STIs attending antenatal care clinics in Delta State, Nigeria. Two research questions were answered and one hypothesis was tested at 95% confidence level. A descriptive survey design was utilized to execute the study. The population for the study was 2280 pregnant women attending ANC in General Hospitals in Delta State diagnosed with STIs (January, 2018-December, 2022). The sample for the study comprised 342 randomly selected pregnant women. A structured questionnaire (HSBPWANCCQ) was used for data collection. The HSBPWANCCQ was validated by three experts while its reliability index o.63 was established using Pearson Product Moment correlation coefficient. Mean () and standard deviation (SD) were used to answer the research questions whereas ANOVA was used to test the hypothesis. Finding showed that there was very high level HSBs among the studied group (=2.41: SD=0.94). Nulliipara (=2.53: SD=0.95) had the highest HSB among all the categories of women. ANOVA revealed that parity made no statistically significant difference in the HSBs of pregnant women infected with STIs in Delta State (p-value=0.990 >0.05 alpha level of significance). Based on the findings a sustained enlightenment of pregnant women on the need to always seek appropriate treatment for STIs was recommended.